Analisis Pengaruh Daya Tarik Toko Tahilalats terhadap Minat Wisatawan Generasi Z Mengunjungi Kawasan Jalan Braga Bandung sebagai Destinasi Wisata Urban (Lembaga Pengembangan Kinerja Dosen, 2025)
Jalan Braga in Bandung is renowned as an urban tourism destination that blends historical ambiance with the evolution of modern popular culture. One of the emerging attractions gaining interest among younger audiences, particularly Generation Z, is the presence of creative concept stores such as the Tahilalats Store. This store not only offers uniquely illustrated merchandise but also serves as a representation of digital culture and youth identity. This context is essential to examine, considering the shifting trend in urban tourism that is increasingly influenced by creative and pop-culture-based attractions. Therefore, this study aims to analyze the influence of the Tahilalats Store's attractiveness on Generation Z tourists' interest in visiting Jalan Braga, Bandung.The research applied a quantitative approach using a survey method with 100 Generation Z respondents. Data analysis was conducted using simple linear regression along with validity, reliability, normality, multicollinearity, heteroscedasticity, and linearity tests. The findings indicate that the attractiveness of the Tahilalats Store has a positive and significant effect on the visiting interest of young tourists. The coefficient of determination (R²) value of 0.397 suggests that 39.7% of the variation in visit intention can be explained by the store's attractiveness, while the remaining 60.3% is influenced by other external factors. Thus, it can be concluded that creative-based establishments like the Tahilalats Store can serve as an effective strategy to enhance urban tourism visits, particularly among the Generation Z demographic.